RANCANG BANGUN E-LEARNING BERBASIS WIX PADA MATA KULIAH SENI MUSIK PRODI PGSD UNIVERSITAS SARJANAWIYATA TAMANSISWA - Ardian Arif (Jurnal JPSD (Jurnal Pendidikan Sekolah Dasar), 2019)
E-learning is one of the trends in internet-based learning today. E-learning becomes a learning system for students to be able to access all learning devices ranging from media, materials, teaching materials, and others using the internet network. Wix is one of the internet-based e-learning applications that can be used free and dynamically. The purpose of this study is as an alternative to the delivery of lecture material in Music Art Courses held at the Sarjanawiyata Tamansiswa University Primary School Teacher Education Program. The development of e-learning uses the Research & Development (R&D) method. The research subjects of students in the sixth semester of the 2016 Music Arts Course by selecting samples using random sampling techniques. Methods of data collection used questionnaires, observations, interviews, and documentation. The questionnaire instrument was used to measure the feasibility of e-learning, while interviews, observations, and documentation to support and collect data during the e-learning trial process. Data on the results of testing the use of e-learning using rating scale obtained the number 1078 which means that e-pseudo is suitable for use in a wider circle. E-pseudo has excellent features such as class discussion, upload, download, and subscribe.